Women's perspectives on disrespect and abuse during facility-based childbirth in Ethiopia: a qualitative study - Yohannes Mehretie Adinew; Janet Kelly; Morgan Smith; Amy Marshall (BMC, 2023)
Abstract Background Disrespect and abuse violates women's basic human rights and autonomy and can traumatize women who are already in a vulnerable position during childbirth and deter them from utilizing skilled care for future childbirth. This study explored women's perspectives on the acceptability of disrespect and abuse during facility-based childbirth in Ethiopia. Methods A qualitative descriptive design using five focus group discussions and fifteen in-depth, semi-structured, interviews was conducted with women between October 2019 to January 2020 in north Showa zone of Oromia region, central Ethiopia. Using purposive sampling, women who had given birth at public health facilities of North Showa zone during the twelve months preceding data collection were recruited, regardless of birth outcome. Inductive thematic analysis using Open Code software was used to explore the perspectives of participants. Results While women reject disrespectful and abusive acts during childbirth generally, they may consider some disrespectful acts as acceptable and or necessary under certain circumstances. Four emerging themes were identified. (1) Disrespect and abuse is not acceptable, (2) Disrespectful and abusive actions are acceptable only if intended to save lives, (3) Disrespectful and abusive actions are an accepted part of everyday practice to prevent complications and adverse outcomes, (4) Disrespectful and abusive actions are necessary to discipline disobedient women. Conclusion Women's perceptions of disrespectful and abusive acts of care providers is deeply rooted within the context of violence in Ethiopia and the societal hierarchies that have systematically disempowered women. Given the pervasiveness of disrespect and abusive actions during childbirth, policymakers, clinical managers and care providers must take these essential contextual and societal norms into account and devise comprehensive clinical interventions that addresses the root causes.